Environmental Impacts of Jatropha curcas Biodiesel in India - Gmünder, Simon (Hindawi Publishing Corporation, 2012)
In the context of energy security, rural development and climate change, India actively promotes the cultivation of Jatropha curcas, a biodiesel feedstock which has been identified as suitable for achieving the Indian target of 20% biofuel blending by 2017. In this paper, we present results concerning the range of environmental impacts of different Jatropha curcas cultivation systems. Moreover, nine agronomic trials in Andhra Pradesh are analysed, in which the yield was measured as a function of different inputs such as water, fertilizer, pesticides, and arbuscular mycorrhizal fungi. Further, the environmental impact of the whole Jatropha curcas biodiesel value chain is benchmarked with fossil diesel, following the ISO 14040/44 life cycle assessment procedure. Overall, this study shows that the use of Jatropha curcas biodiesel generally reduces the global warming potential and the nonrenewable energy demand as compared to fossil diesel. On the other hand, the environmental impacts on acidification, ecotoxicity, eutrophication, and water depletion all showed increases. Key for reducing the environmental impact of Jatropha curcas biodiesel is the resource efficiency during crop cultivation (especially mineral fertilizer application) and the optimal site selection of the Jatropha curcas plantations.